Mechanism and Basis of Traditional Chinese Medicine Against Obesity: Prevention and Treatment Strategies - Zhang, Chang-hua; Sheng, Jun-qing; Xie, Wei-hua; Luo, Xiao-quan; Xue, Ya-nan; Xu, Guo-Liang; Chen, Chen (Frontiers in Pharmacology, 2021)
In last few decades, the incidences of obesity and related metabolic disorders worldwide have been increased dramatically. Major pathophysiology of obesity is termed “lipotoxicity” in modern western medicine (MWM) or “dampness-heat” in traditional Chinese medicine (TCM). “Dampness-heat” is a very common and critically important syndrome to guild clinical treatment in TCM. However, the pathogenesis of obesity in TCM is not fully clarified, especially by MWM theories and comparison between TCM and MWM. In this review, the mechanism underlying the action of TCM in the treatment of obesity and related metabolic disorders was thoroughly discussed, and prevention and treatment strategies were proposed accordingly. Hypoxia and inflammation caused by lipotoxicity exist in obesity and are key pathophysiological characteristics of “dampness-heat” syndrome in TCM. “Dampness-heat" is prevalent in chronic low-grade systemic inflammation, prone to insulin resistance (IR), and causing variant metabolic disorders. In particular, the MWM theories of hypoxia and inflammation were applied to explain the “dampness-heat” syndrome of TCM, and we summarized and proposed the pathological path of obesity – lipotoxicity - hypoxia or chronic low-grade inflammation - IR - metabolic disorders. This provides significant enrichment to the scientific connotation of TCM theories and promotes the modernization of TCM.